Pi'uranga: Study of Cia-Cia's Nifas Period Treatment in the Bahari Village of Sampolawa District of South Buton Regency - Hasniah; La Ode Topo Jers; Wa Mame; Jamaluddin Hos (Indonesian Journal of Social and Environmental Issues (IJSEI), 2020)
This research aims to find out the types of diseases that arise when the mother nifas does not do pi'uranga and how to perform pi'uranga on the Cia-cia in the Bahari Village. The theory used to read the data is Hippocrates' Humoral Pathology theory of healthiness or pain occurring depending on the balance of "humour" (fluid) in the body. The study used ethnographic methods, data obtained through engaged observations, and in-depth interviews. The results showed that: (1) A disease that arises when the mother nifas does not do pi'urangawas known by the term puanaka, which consists of an old puanaka and a young puanaka. Symptoms of old puanaka include chills, difficulty standing, abdominal pain, and headaches, while young puanaka is characterized by loss of consciousness, cysts, and serious illnesses. (2) The way the implementation of pi'uranga in the Cia-cia in Bahari Village was done traditionally, through several stages; beginning with the mother nifas sorted by the shaman, the first bath after childbirth, the use of octopuses, the use of fireplaces, the use of folk remedies, to the sauna.